2021
DOI: 10.3390/ijerph18041822
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Adherence to Governmental COVID-19 Measures among Danish Students?

Abstract: Knowledge on compliance with governmental recommendations in combating the spread of COVID-19 in different groups is important to target efforts. This study investigated the adherence to the governmental implemented COVID-19 measures and its predictors in Danish university students, a not-at-risk group for COVID-19 mortality and normally characterized by many social contacts. As part of the COVID-19 International Student Wellbeing Study, a survey on socio-demographic situation, study information, living arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
4
30
1
Order By: Relevance
“…As expected, in both male and female participants, a negative relationship was observed between depressive symptomatology and adherence to safety measures. This is, however, not in line with the observations made in some similar studies, where participants with high adherence to precautionary measures were found to exhibit higher rates of depressive symptoms [26,29], but it is in line with some other studies where higher compliance was found to be related to lower depression [33]. One possible reason for our study observation is that students' confidence about government-implemented precautionary measures may have lowered their stress levels in relation to the disease.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…As expected, in both male and female participants, a negative relationship was observed between depressive symptomatology and adherence to safety measures. This is, however, not in line with the observations made in some similar studies, where participants with high adherence to precautionary measures were found to exhibit higher rates of depressive symptoms [26,29], but it is in line with some other studies where higher compliance was found to be related to lower depression [33]. One possible reason for our study observation is that students' confidence about government-implemented precautionary measures may have lowered their stress levels in relation to the disease.…”
Section: Discussioncontrasting
confidence: 94%
“…This study’s results also indicate a considerable gender difference in the prevalence of depressive symptoms among the participants. Many studies have indicated that women are at higher risk of developing depressive symptoms [ 29 , 30 ], and the same was observed among female undergraduates during the pandemic [ 29 ]. Although, a slightly higher percentage of male undergraduates reported elevated depressive symptoms than that of female undergraduates in our study sample, the mean score of the CES-D is significantly higher in female undergraduates than that of male undergraduates.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Surveys on college students can be found in [19][20][21][22][23]. In [19], the authors studied 2739 students from China and Hong Kong and found that the COVID-19 pandemic had significantly reduced students' interest in studying abroad.…”
Section: Related Workmentioning
confidence: 99%